Artemisinin‐derived dimers from a chemical perspective. Issue 6 (11th June 2021) - Çapcı, Aysun; Herrmann, Lars; Sampath Kumar, Halmuthur M.; Fröhlich, Tony; Tsogoeva, Svetlana B.
Abstract: Considerable progress has been made with the rather recently developed dimer approach, which has already found applications in the development of new effective artemisinin‐derived antimalarial, anticancer, and antiviral agents. One observation common to these potential applications is the significant (i.e., much more than double) improvement in activity of artemisinin based dimers, which are not toxic to normal cells and have fewer or less harmful side effects, with respect to monomers against parasites, cancer cells and viruses. Due to the high potential of the dimerization concept, many new artemisinin‐derived dimer compounds and their biological activities have been recently reported. In this review an overview of the synthesis of dimer drug candidates based on the clinically used drug artemisinin and its semisynthetic derivatives is given. Besides the highlighting of biological activities of the selected dimers, the main focus is set on different synthetic approaches toward the dimers containing a broad variety of symmetric and nonsymmetric linking moieties.